(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Musculoskeletal System Disorders (MSDs) are one of the most common occupational diseases experienced by workers. This disorder is influenced by several factors, such asrepetitive activity factor and unnatural work attitude factor. The purpose of this study was to analyze the strong relationship between work attitude and repetitive activity with subjective complaints of musculoskeletal disorder in the circular loom division of PT. Kerta Rajasa Raya Sidoarjo, Indonesia. This study used observational techniques with cross-sectional design. Respondents in this study were workers in the circular loom division of PT. Kerta Rajasa Raya, Sidoarjo, that consisted of 14 people based on the researchers’ inclusion criteria. The data were obtained from the results of questionnaires and field observations. Work attitude data were analyzed using OWAS; MSDs subjective complaint data were investigated using NBM checklist sheets; and repetitive activity data were analyzed based on the results of questionnaires, interviews, and observations. The results showed that the majority of respondents have subjective complaints of musculoskeletal disorder with high severity. The work attitude variable has a very strong correlation with subjective complaints of MSDs, and repetitive activity variable has a strong correlation with subjective complaints of MSDs. The company are advised to provide training related to safe lifting method, provide information related to MSDs in the form of posters or providing specific material. Companies are also advised to add the expedition personnel to reduce the repetition of lifting activities.